2019
DOI: 10.31557/apjcc.2019.4.4.125-130
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practice of Cervical Cancer Prevention among Student Health Professionals in Nigeria

Abstract: Background: Cervical cancer is the second most commonly diagnosed gynecological cancer affecting women worldwide. It is a preventable disease but still remains a leading cause of cancer deaths in developing countries like Nigeria despite the availability of preventive strategies. Undergraduate pharmacy and medical students are future health care providers who can help raise awareness and improve the knowledge of the public towards cervical cancer, its screening, prevention and treatment. The study sought to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
3
6
0
Order By: Relevance
“…Given that the Nigerian 6-3-3-4 educational system mandates a minimum age of 16 for university enrolment, this result was expected. Consistent with several other studies among undergraduates, the vast majority of participants in the current study were also single (94.5%) (Amukugo et al, 2018;Anene-Okeke et al, 2019;Shetty et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Given that the Nigerian 6-3-3-4 educational system mandates a minimum age of 16 for university enrolment, this result was expected. Consistent with several other studies among undergraduates, the vast majority of participants in the current study were also single (94.5%) (Amukugo et al, 2018;Anene-Okeke et al, 2019;Shetty et al, 2019).…”
Section: Discussionsupporting
confidence: 90%
“…More than half of the participants claimed to have never had sex, consistent with the results of similar research among undergraduate Nigerian students (Anene-Okeke et al, 2019). In contrast, findings from a study among Namibian undergraduates showed that most respondents were sexually active (Amukugo et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…This was consistent with other studies showing that women’s awareness of cervical cancer screening and HPV vaccination was low before the intervention [ 37 39 ]. Still, some other studies showed divergent findings as they reported a high level of awareness of cervical cancer and Pap test administration among women [ 40 , 41 ]. These contradictory findings can be explained by participants’ different demographic information, as Aweke et al included educated women in their research, whose knowledge and awareness were certainly higher than the average population.…”
Section: Discussionmentioning
confidence: 99%